IMPLEMENTASI KEBIJAKAN PENGEMBANGAN PARIWISATA DALAM KAWASAN KONSERVASI TAMAN PESISIR PANTAI UJUNG NEGORO BATANG - Mesha Rahma Aurellita; Titik Djumiarti; Dyah Lituhayu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
Batang Regency is one of the areas in Central Java Province which has many places, one of which is the Ujungnegoro Beach tourist attraction which is also a conservation area. However, it can be said that the development of tourism in Ujungnegoro Beach has not been maximized, such as the Sapta Pesona program that has not been achieved as stated in the Decree of the Minister of Tourism, Post and Telecommunications Number: KM.5/UM.209/MPPT-89, namely in terms of cleanliness, beauty, coolness and memories, as well as management that is less than optimal, there are limitations in tourism development because these attractions are included in the conservation area. This study aims to determine the implementation of policies in the Ujungnegoro Coastal Park Conservation Area, as well as identify the influencing factors. This research use desciptive qualitative approach. Data collection techniques through interviews, observation, and documentation and using domain analysis. Based on the results of the research, it shows that the implementation of tourism development policies at Ujungnegoro Beach has not been fully implemented based on 5 accuracy by Riant Nugroho which has been described in the discussion where the accuracy of the policy has not been maximized. The recommendation in this study is that the tourism office can collaborate to increase the budget so that it can update infrastructure, carry out routine checks on infrastructure and maintain relationships between implementers.